Assessment of conservation status of Ferula huber‐morathii: association with population genetic structure and regional climate - Keser, Ali Murat; Demir, İbrahim (Nordic journal of botany, 2025)
Ferula huber‐morathii is an endemic and medicinally important plant. This species is distributed in eight Turkish localities, including three newly identified ones. Its extent of occurrence and area of occupancy is determined to be 3963 km2 and 32 km2 respectively. All localities are characterized by East Mediterranean and sub‐Mediterranean precipitation regimes; however, temperatures increase excessively and precipitation decreases during the flowering period of the species. The population sizes are quite small, and the number of reproducing individuals in some populations is below ten. Analyses of ISSR markers showed the percentage of polymorphic loci to be 94% at the species level and 56% at the population level. The level of genetic differentiation (measured by GST) was 0.37 and the estimated level of gene flow among populations (NM) was 0.84. The percentage of variance occurring within and among populations, determined by AMOVA, was 75% and 25%, respectively. STRUCTURE analysis revealed two genetic clusters of individuals with a geographic structure, similar to that found in UPGMA and an ordination analysis. Some populations turned out to have both low numbers of individuals and low genetic diversity. Since many of the populations are subject to anthropogenic disturbance, the species should remain in the EN category. At the same time, it is suggested that a new in‐situ conservation area should be created around nearby dams, situated in the same climate area as the currently known populations.